Multilingualism in Lithuanian cities: aims and outcomes of a home language survey in Vilnius, Kaunas and Klaipėda - Ramonienė, Meilutė; Extra, Guus (Kalbotyra, 2011)
On the basis of the experience gained from the Multilingual Cities Project, carried out in 6 Western European multicultural cities (Extra & Yağmur 2004), a home language survey was carried out at almost all primary schools in Vilnius, Kaunas and Klaipėda. The total sample consists of almost 24,000 pupils, most of them in the age range of 8-10 years old. After an introduction to the aims of the project, the design of the questionnaire and the collection, processing and analysis of the resulting data, information will be provided on the size and composition of the sample and the distribution of reported home languages. The top-9 of reported languages contains the vast majority of all home languages referred to, i.e., Lithuanian, Russian, English, Polish, German, Belarusian, French, Ukrainian, and Latvian. For these 9 languages groups, crosslinguistic perspectives will be offered on language profiles and language vitality in terms of reported language proficiency, language choice, language dominance, and language preference. Pseudolongitudinal perspectives will be offered for each of these four dimensions in the age range of 8-10 years old.
Keywords: language choice; language dominance; language preference; language proficiency; language profiles; language survey; language vitality